2013
DOI: 10.3390/ma6125742
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Ferrocene-Modified Thin Films and Nanoparticles for Biosensors

Abstract: This article reviews recent progress in the development of ferrocene (Fc)-modified thin films and nanoparticles in relation to their biosensor applications. Redox-active materials in enzyme biosensors commonly use Fc derivatives, which mediate electron transfer between the electrode and enzyme active site. Either voltammetric or amperometric signals originating from redox reactions of Fc are detected or modulated by the binding of analytes on the electrode. Fc-modified thin films have been prepared by a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 151 publications
(197 reference statements)
1
43
0
Order By: Relevance
“…Organic and inorganic nano-and micro-particles have been extensively studied for the development of catalysts, biosensors, reagents for imaging, and drug delivery systems [1][2][3][4][5][6][7][8]. CaCO 3 microspheres are widely used owing to their facile preparation, biocompatibility, and low cost [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Organic and inorganic nano-and micro-particles have been extensively studied for the development of catalysts, biosensors, reagents for imaging, and drug delivery systems [1][2][3][4][5][6][7][8]. CaCO 3 microspheres are widely used owing to their facile preparation, biocompatibility, and low cost [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These functionalized ferrocene derivatives and their metal complexes represent an important topic of research in many fields such as organic synthesis, catalysis, asymmetric catalysis, materials chemistry, and in medicine as antimalarial or antitumor agents. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In particular, ferrocenyl phosphines have been studied thoroughly, as represented by the well-known 1,1′-bis(diphenylphosphino)ferrocene (dppf ). [1] Some of us have described the formation of several amidephosphines containing ferrocene units, studied their coordination chemistry, [17,18] and also showed that some gold and silver complexes are active as antitumor agents.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanomaterials and electron transfer relays in realizing the electron exchange from biological redox centre has been an active area of research having potentiality for the evolution of commercial biocompatible technology [1][2][3][4][5][6][7][8]. Extensive reports on the use of ferrocene and its derivatives as electron transfer mediator are documented during last three decades, justifying the commercial design of electrochemical biosensors [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%